2008
DOI: 10.3324/haematol.11655
|View full text |Cite
|
Sign up to set email alerts
|

Long-term response and outcome following immunosuppressive therapy in thymoma-associated pure red cell aplasia: a nationwide cohort study in Japan by the PRCA collaborative study group

Abstract: BackgroundThymoma-associated pure red cell aplasia (PRCA) accounts for a significant proportion of cases of secondary PRCA and immunosuppressive therapy has been reported to be useful in this condition. However, because of its rarity, the long-term response and relapse rates after immunosuppressive therapy are largely unknown, and optimal management of this disorder remains unclear. The aim of this study was to collect more information on the outcome of patients with thymoma-associated PRCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 18 publications
3
68
2
Order By: Relevance
“…We have reported that the discontinuation of maintenance CsA therapy is strongly correlated with relapse in idiopathic PRCA patients, 3 and that thymoma-associated PRCA may also be CsA-dependent. 13 In the present study, there were 3 patients who maintained remission after the discontinuation of CY; however, each relapse-free period after the discontinuation was still only 0, 6 and 11 months. Considering that a relapse can occur even 39 months after the discontinuation of CY, these observation periods may be insufficient to conclude that LGL-leukemia can be cured by CY.…”
Section: Mortality and Overall Survivalcontrasting
confidence: 48%
See 2 more Smart Citations
“…We have reported that the discontinuation of maintenance CsA therapy is strongly correlated with relapse in idiopathic PRCA patients, 3 and that thymoma-associated PRCA may also be CsA-dependent. 13 In the present study, there were 3 patients who maintained remission after the discontinuation of CY; however, each relapse-free period after the discontinuation was still only 0, 6 and 11 months. Considering that a relapse can occur even 39 months after the discontinuation of CY, these observation periods may be insufficient to conclude that LGL-leukemia can be cured by CY.…”
Section: Mortality and Overall Survivalcontrasting
confidence: 48%
“…As described elsewhere, 3,13 the questionnaires were sent to 109 hematology departments in Japan, and a total of 185 evaluable patients were collected from 45 institutions. Seventy-three patients were classified as having idiopathic PRCA and 112 patients had secondary PRCA.…”
Section: Data Collection Of the Data And Patients' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the heterogeneity of its pathogenesis, most PRCA patients respond to monotherapy with CsA [7,37,38]. The reason for the uniform response to CsA and the target of CsA remain unknown.…”
Section: Foxp3mentioning
confidence: 99%
“…In this symposium, based on a nationwide survey in Japan, current strategies for the treatment of PRCA were introduced in a presidential lecture. Although this issue is not reviewed in this PIH series, relevant articles can be found elsewhere [21,22] as can focused articles on idiopathic [23], thymoma-associated [24], large granular lymphocyte leukemia-associated [25] and lymphoma-associated PRCA [26]. Oligodeoxynucleotides (ODN) are another deserving wonder that does not appear in this PIH series.…”
Section: Heme and Ironmentioning
confidence: 99%